北極の海氷減少と南極の海氷増加 -両極のトレンドと季節変化の比較 - 榎本, 浩之 (2016)
Firstly the study the study introduce long-term trends of sea ice extent in the Arctic and Southern Ocean, their trends, seasonal variations. Then report on the sea ice condition in the southern ocean in the last season. Sea ice variations in the Arctic and in the Southern Ocean Sea ice data is indicated usually separated in the Arctic or Antarctic. This study tried to put together and summarized characteristics of their extent, seasonal differences, seasonal march and long-term trends. Although the sea ice in the Southern Ocean has increasing trend, this increasing trend is not enough to compensate the decreasing trend in the Arctic, The total sea ice in the polar regions has decreased. However total ice extent variation was modified by the seasonal march of sea ice extent in the Southern Ocean. The winter to autumn extent in the Southern Ocean leaded total sea ice area in October and November. This is due to the diverging ice field in the Southern Ocean. Sea ice area around Antarctic Continent can be separated in to several zones by latitude and season. Ice dynamics are important factor in the Antarctic sea ice change due to its high mobility. Sea ice in the Arctic is surrounded by continents and has been neither dynamic nor diverging before. It fills Arctic Ocean in winter, and it was thick. Arctic sea ice was thick and their mobility was not large, however recent decrease of ice area is making new condition of Arctic sea ice. Sea ice in the Arctic is now showing high mobility in summer and also evidenced even in winter season. Recent study introduces importance of sea ice dynamics for the ice thickness change in the Arctic. Sea ice conditions in 2015 in the Antarctic In 2014 the sea ice in the southern ocean had the record maximum of the extent since the satellite observation has started. However sea ice extent in the 2015 was almost minimum in mid-winter season. The extreme event happened in middle of July, and sea ice extent quitted. Air temperature in the Syowa station was very low in early July -37, then ...